Kajian Stilistika: Analisis Diksi Serat Sabdajati Karya R. Ng. Ranggawarsita - Ridho Bayu Kurniawan (Jurnal Online Baradha, 2026)
This study is based on the limited range of stylistic elements (diction) that are commonly known. The aesthetic elements of language that are generally recognized are limited to figures of speech and other stylistic devices. However, beyond that, the Javanese language possesses a distinctive style of word usage commonly found in classical texts, one of which is Serat Sabdajati by R. Ng. Ranggawarsita. This is what distinguishes Javanese literary works, endowing them with richness in both language and meaning. This study aims to describe the stylistic features in *Serat Sabdajati* by R. Ng. Ranggawarsita using a qualitative descriptive research method. The data were analyzed and described using a stylistic approach. The results revealed 64 unique Javanese stylistic features that differ from those in literary works in other languages. The study identified 43 instances of archaic affixation, predominantly infixes; 1 instance of a saroja compound; 5 instances of a garba compound; 5 instances of an entar compound; 4 instances of Kawi compounds; 13 instances of dasanama; and 5 instances of sandi asma. The entirety of the data found and described demonstrates the unique, diverse, and meaningful stylistic features of classical Javanese literary works, each serving specific purposes.